IMPLEMENTATION OF AI-BASED CHATBOT AS A CUSTOMER SERVICE MANAGEMENT INFORMATION SYSTEM - Dwi Silvia Ningsih; Muhammad Irwan Padli Nasution (CV. Barokah Publsiher, 2025)
The development of digital technology has led to the emergence of chatbots that use Artificial Intelligence (AI) as an innovation in customer service management information systems. This study aims to explain how AI-based chatbots are used to improve service effectiveness and company operational efficiency. The method used is an analysis of various relevant sources. The results show that chatbots are capable of providing fast, responsive, and 24-hour service, thereby increasing customer satisfaction and reducing company operational costs. However, chatbots still have shortcomings in understanding user sentiment and require regular system updates. Overall, the implementation of AI-based chatbots has a positive impact on improving service quality and the effectiveness of management information management.